Does Personality Matter in Diabetes Adherence? Exploring the Pathways between Neuroticism and Patient Adherence in Couples with Type 2 Diabetes. Issue 2 (12th April 2017) - Novak, Joshua R.; Anderson, Jared R.; Johnson, Matthew D.; Hardy, Nathan R.; Walker, Ann; Wilcox, Allison; Lewis, Virginia L.; Robbins, David C.
Abstract : Background: Personality has received some attention in the Type 2 diabetes literature; however, research has not linked personality and diabetes adherence behaviors (diet and exercise), identified pathways through which they are associated, nor taken into consideration important contextual factors that influence behavior (the patient's partner). Methods: Dyadic data from 117 married, heterosexual couples in which one member is diagnosed with Type 2 diabetes was used to explore associations between each partner's neuroticism and patient dietary and exercise adherence through the pathways of negative affect, depression symptoms, and couple‐level diabetes efficacy (both patient and spouse report of confidence in the patient's ability to adhere to diabetes management regimens). Results: Results revealed that higher levels of neuroticism were associated with lower patient dietary and exercise adherence through (1) higher levels of depression symptoms (for patients' neuroticism) and negative affect (for spouses' neuroticism), and (2) lower levels of couple‐level diabetes efficacy. Conclusions: The results from this study provide evidence that both patient and spouse personality traits are associated with patient dietary and exercise adherence through increased emotional distress—albeit different emotional pathways for patients and spouses—and lower couple confidence in the patients' ability to manage their diabetes.